Reliability of printed stretchable electronics based on nano/micro materials for practical applications - Lv, Jian (2023)
Recent decades have witnessed the booming development of stretchable electronics based on nano/micro composite inks. Printing is a scalable, low-cost, and high-efficiency fabrication tool to realize stretchable electronics through additive processes. However, compared with conventional flexible electronics, stretchable electronics need to experience more severe mechanical deformation which may cause destructive damage. Most of the reported works in this field mainly focus on how to achieve a high stretchability of nano/micro composite conductors or single working modules/devices, with limited attention given to the reliability for practical applications. In this minireview, we summarized the failure modes when printing stretchable electronics using nano/micro composite ink, including dysfunction of the stretchable interconnects, the stress-concentrated rigid-soft interfaces for hybrid electronics, the vulnerable vias upon stretching, thermal accumulation, and environmental instability of stretchable materials. Strategies for tackling these challenges to realize reliable performances are proposed and discussed. Our review provides an overview on the importance of reliable, printable, and stretchable electronics, which are the key enablers in propelling stretchable electronics from fancy demos to practical applications.